2020
DOI: 10.1002/essoar.10503825.1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mantle and crustal sources of magmatic activity of Klyuchevskoy and surrounding volcanoes in Kamchatka inferred from earthquake tomography

Abstract: Klyuchevskoy and surrounding volcanoes in central Kamchatka form the Northern Group of Volcanoes (NGV), which is an area of particularly diverse and intensive Pleistocene-Holocene volcanism. In this study, we present a new seismic tomographic model of the crust and uppermost mantle beneath NGV based on local earthquake data recorded by several permanent and temporary seismic networks including a large-scale experiment that was conducted in 2015-2016 by an international scientific consortium. Having an unprece… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 56 publications
(80 reference statements)
0
9
0
Order By: Relevance
“…Based on the data of permanent seismic stations operated by the KBGS and several temporary seismic networks installed in the vicinity of Bezymianny and its neighboring volcanoes of the KGV, previous studies 29 – 35 revealed multilevel magma storages in the crust and the uppermost mantle: the shallow-most level being located at circa 8 km depth. Multiple petrological studies 36 , 37 revealed consistent storage conditions of magmas for Bezymianny, but they could not yet characterize the lateral complexity and dimensions of potential reservoirs.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the data of permanent seismic stations operated by the KBGS and several temporary seismic networks installed in the vicinity of Bezymianny and its neighboring volcanoes of the KGV, previous studies 29 – 35 revealed multilevel magma storages in the crust and the uppermost mantle: the shallow-most level being located at circa 8 km depth. Multiple petrological studies 36 , 37 revealed consistent storage conditions of magmas for Bezymianny, but they could not yet characterize the lateral complexity and dimensions of potential reservoirs.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the mantle plume effect induced partial melting of the subducting plate in the western part of the Aleutian arcs to form a zone (so-called slab portal) in which the subducting plate is absent [6]. The presence of the ascending asthenospheric flow in the junction between the Kuril-Kamchatka and Aleutian island arcs has been verified recently by modeling on the basis of body-wave seismic tomography [7]. The reconstruction of mantle melt supply at the boundary of the subducting plate is shown in Fig.…”
mentioning
confidence: 87%
“…This anomaly can be considered as an intrusion of magmatic melts along the subduction zone from the vertical asthenospheric flow at the boundary of the subducting slab. The pattern of the velocity structure presented in [7] could be obtained only for the Kizimen volcano area. The observation system used did permit construction of seismotomographic models for volcanoes of the Eastern volcanic belt of Kamchatka, which were located to the south of Kizimen.…”
mentioning
confidence: 99%
“…Since it is widely accepted that the shear modulus and S-wave velocity are most affected by the presence of melt (or more generally fluid fraction), the S-wave seismic tomography is particularly suitable to image the regions with presence of significant portions of melt such as in mid-oceanic ridges (e.g., Conder et al, 2002) hotspots (Allen et al, 2002). Strong negative P-wave seismic velocity anomalies can also indicate the presence of melt, especially beneath volcanoes, and in many cases, the Vp/Vs ratio is used to trace the melts (e.g., Koulakov et al, 2020). Melt-induced variations of the elastic moduli also affect the reflectivity structure in the crust and in the uppermost mantle.…”
Section: Introductionmentioning
confidence: 99%